Reproductive and agronomic characterization of novel apomictic hybrids of Paspalum (Poaceae) - Brugnoli, Elsa Andrea (2023)
The tetraploid germplasm of Paspalum contains a large diversity that can be used to generate better forages. The objective was to evaluate a group of Paspalum notatum and P. simplex apomictic hybrids for a set of agronomic traits and apomixis expressivity. Forage yield, cold tolerance, winter regrowth and seed yield were evaluated. Expressivity of apomixis was evaluated in P. simplex hybrids by flow cytometry. Progeny test with molecular markers was used to determine the genotypic variability in the progeny. Differences within P. notatum and P. simplex hybrids were observed for all traits and some of them were superior in comparison with the controls. The accumulated forage yield during three years was 988 g m-2, in the P. notatum hybrids, whereas in P. simplex the average forage yield per harvest was 180 g m-2. In P. simplex, the apomixis expressivity varied between 0 and 100%, and 65% of the hybrids showed high apomixis expressivity (superior to 70%). The genotypic mean homogeneity in the progeny was 76% and 85% in P. notatum and simplex respectively. The generation of hybrids with high apomixis expressivity that combine good agronomic performance and homogeneity in the offspring is possible in tetraploid P. notatum and P. simplex.